AGAMA DAN MASALAH KORUPSI : - Herdi Sahrasad (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2017)
One of the most serious social problems in this country is corruption. From New Order to Reformation today, corruption continues craze and for the most part, due to lack of morals and integrity of officials, politicians and businessmen who are often easily slip into the trap of corruption. Consequently, in Indonesia, Muslims as a majority of the people, is still suffering and marginalized due to rampant corruption, feudalism power, and political-economic structures that lame. Admittedly, in this reform era, corruption was threatening the safety of the nation so much shouting that stern action be taken against the corrupt and violent. This paper would like to provide critical remarks about religion and the problem of corruption in Indonesia. KEY WORDS:Corruption, Religion, Moral and Integrity, Official, Politician, Businessmen, KPK